2004
DOI: 10.1097/01.md.0000126763.68170.46
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course and Flow Cytometric Analysis of Paroxysmal Nocturnal Hemoglobinuria in the United States and Japan

Abstract: : To determine and directly compare the clinical course of white and Asian patients with paroxysmal nocturnal hemoglobinuria (PNH), data were collected for epidemiologic analysis on 176 patients from Duke University and 209 patients from Japan. White patients were younger with significantly more classical symptoms of PNH including thrombosis, hemoglobinuria, and infection, while Asian patients were older with more marrow aplasia. The mean fraction of CD59-negative polymorphonuclear cells (PMN) at initial analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
194
2
29

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 219 publications
(245 citation statements)
references
References 41 publications
16
194
2
29
Order By: Relevance
“…[1][2][3][4] In the last 2 decades, virtually the entire mechanism leading to PNH hemolysis has been elucidated. [5][6][7][8] PNH stem cells acquire PIGA mutations and do not generate glycosylphosphatidylinositol (GPI), resulting in a deficiency of a series of GPI-linked membrane proteins, including complement regulatory molecules such as decay-accelerating factor (DAF) and CD59.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In the last 2 decades, virtually the entire mechanism leading to PNH hemolysis has been elucidated. [5][6][7][8] PNH stem cells acquire PIGA mutations and do not generate glycosylphosphatidylinositol (GPI), resulting in a deficiency of a series of GPI-linked membrane proteins, including complement regulatory molecules such as decay-accelerating factor (DAF) and CD59.…”
Section: Introductionmentioning
confidence: 99%
“…9 On the other hand, more than half of patients with PNH show various cytopenias and decreased CD34 ϩ hematopoietic cells. [1][2][3][4][10][11][12] PNH closely associates with aplastic anemia and myelodysplastic syndromes (MDSs) that share BM failure and development of leukemia. 1,12,13 It has been indicated that immune-mediated BM injury underlies at least a part of the diseases.…”
mentioning
confidence: 99%
“…(15). Two large studies have shown that in all patients with thrombosis, the PNH clone in granulocytes was greater than 50% and 61% respectively (15,16). However, in some studies, PNH clones have been reported at much lower levels in patients with thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The association between HA and antiphospholipid antibodies remains a focus of research on AFAS (14). (15). Two large studies have shown that in all patients with thrombosis, the PNH clone in granulocytes was greater than 50% and 61% respectively (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Eculizumab, an inhibitor of terminal complement C5, provides patients with PNH with a good quality of life by ameliorating hemolysis and thrombosis, and promotes a better understanding of the complement-mediated molecular pathophysiology of PNH [1][2][3]. However, the underlying reasons for distinct differences in the incidences of thrombosis and bone marrow failure between Caucasian and Asian patients with PNH are still unknown (West vs. Japan, 32% vs. 4%) [4]. Racial differences are more evident in PNH thrombosis than in other conventional arterial thromboses (PNH vs. others, 2.4 to 9.8 vs. 1.7 to 3.9-fold increase) [4,5], suggesting that the presence of thrombus formation is characteristic of PNH.…”
mentioning
confidence: 99%